Penerapan Model Group Investigation Untuk Meningkatkan Keterampilan Berdiskusi di Kelas Tinggi - Dista Aprilia; Dyah Lyesmaya; Andi Nurochmah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
This study aims to describe improvement in students' discussion skills through the Group Investigation learning model in high class. The research method used was Classroom Action Research (CAR) with a research design using the Kemmis and Mc models. Taggart conducted two cycles. The research instruments used were discussion skills questionnaires, teacher activity observation sheets, student activity observation sheets, and observation skills discussion sheets. The results of the study show that the application of the Group Investigation learning model can improve students' high-level discussion skills. Based on the research that has been done, the results obtained from the pre-cycle students with a value of 69%, increased in the first cycle with a value of 73%, and in the second cycle reached 81%. Thus the application of the Group Investigation learning model can improve the discussion skills of students in the high class.